2022
DOI: 10.1101/2022.02.21.22271272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community-based Case Studies of Vaccine Hesitancy and the COVID-19 Response in South Africa; The VaxScenes Study

Abstract: Background South Africa has reported more than half of all COVID-19 cases and deaths in Africa. The South African government has launched a large COVID-19 immunization campaign with the goal of reaching more than 40 million individuals. Nonetheless, certain international, largely internet-based surveys have shown a significant proportion of vaccine hesitancy in South Africa. This study aims to determine and co-create with local stakeholders a comprehensive understanding of vaccine hesitancy and opportunities… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…We also deposited an earlier version of the study proposal in a preprint server. 46 Data availability Extended data Figshare: Questionnaires for the "Community -based case studies of vaccine hesitancy and the COVID-19 response in South Africa" https://doi.org/10.6084/m9.figshare.21548826.v1. 47 This project contains the following extended data: -Data_BeSD_in_RSA_Wiysonge_14nov2022.docx (All interview, focus group and questionnaire tools) Data are available under the terms of the Creative Commons Attribution 4.0 International license (CC-BY 4.0).…”
Section: Dissemination Plansmentioning
confidence: 99%
“…We also deposited an earlier version of the study proposal in a preprint server. 46 Data availability Extended data Figshare: Questionnaires for the "Community -based case studies of vaccine hesitancy and the COVID-19 response in South Africa" https://doi.org/10.6084/m9.figshare.21548826.v1. 47 This project contains the following extended data: -Data_BeSD_in_RSA_Wiysonge_14nov2022.docx (All interview, focus group and questionnaire tools) Data are available under the terms of the Creative Commons Attribution 4.0 International license (CC-BY 4.0).…”
Section: Dissemination Plansmentioning
confidence: 99%
“…Rural communities, with fewer providers and limited facilities, also struggle to access healthcare services, impacting immunisation rates [ 18 , 29 , 30 ]. Social norms perpetuate false narratives and vaccine conspiracy theories, reducing the intention to immunise [ 21 , 31 ]. Myths within communities, such as concerns about live viruses or autism links, contribute to negative perceptions of vaccines.…”
Section: Introductionmentioning
confidence: 99%
“… 13 For example, we have found that practical challenges around access and logistical issues pertaining to vaccination services are major contributors to COVID-19 vaccine hesitancy in the country. 6 , 7 Specifically, questions of geography, transport and other (opportunity) costs associated with accessing vaccination services, long queues and waiting times at vaccination services, and difficulties around navigating the online registration system all impacted on people’s unwillingness to get vaccinated. There is therefore a need for ongoing and enhanced strategies which target the structural and service-level factors that hinder access and convenience around COVID-19 vaccination.…”
mentioning
confidence: 99%
“…We have also found that experiences of poverty and marginalization may provide a fertile ground for COVID-19 vaccine hesitancy in South Africa. 6 The pandemic has had dire economic consequences, including generating or exacerbating poverty, food insecurity, a lack of social support, unemployment and a real sense of hopelessness for so many individuals and communities. 27 Context matters.…”
mentioning
confidence: 99%
See 1 more Smart Citation